2022
DOI: 10.1038/s41598-022-26795-7
|View full text |Cite
|
Sign up to set email alerts
|

A bile acid-related prognostic signature in hepatocellular carcinoma

Abstract: Due to the high mortality of hepatocellular carcinoma (HCC), its prognostic models are urgently needed. Bile acid (BA) metabolic disturbance participates in hepatocarcinogenesis. We aim to develop a BA-related gene signature for HCC patients. Research data of HCC were obtained from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) online databases. After least absolute shrinkage and selection operator (LASSO) regression analysis, we developed a BA-related prognostic signature in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 58 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…This may be one of the mechanisms by which IMCC occurs. Previous studies also support our speculation (12,13). A Gene Set Enrichment Analysis (GSEA) was also performed, which showed that oxygen-linked mucin glycosylation was activated in IMCC (Figure 1C).…”
Section: Transcriptome Characteristics Of Imccsupporting
confidence: 88%
“…This may be one of the mechanisms by which IMCC occurs. Previous studies also support our speculation (12,13). A Gene Set Enrichment Analysis (GSEA) was also performed, which showed that oxygen-linked mucin glycosylation was activated in IMCC (Figure 1C).…”
Section: Transcriptome Characteristics Of Imccsupporting
confidence: 88%
“… 50 Moreover, several reported molecular signatures and computational models based on bile acid metabolism-related genes were found to effectively predict the prognosis of HCC patients and their immunotherapeutic response. 50 , 51 , 52 , 53 , 54 A few available reports hint the possibility that bile acid metabolism could explain sex divergences in liver disease pathologies. One 2007 study highlights a female-specific resistance in hepatotoxic and cholestasis mouse models due to their better bile acid detoxification.…”
Section: Discussionmentioning
confidence: 99%